영재학교의 수학 중심 융합 교육과정 평가 사례 연구 - 정민석; 고호경 (East Asian Mathematical Journal, 2018)
There is currently a growing need to nurture creative and convergent talent in the face of the fourth Industrial Revolution. Developing such talent requires interdisciplinary convergent education across the science, engineering, humanities, social studies, and arts disciplines. Such interdisciplinary convergence could cultivate humanities and social knowledge and qualities along with scientific expertise. In Korea, there are currently six science schools for the gifted that aim to discover and nurture science, technology, engineering, and mathematics (STEM) researchers from an early stage, and two science and art schools for the gifted that aim to cultivate new talent combining students’ scientific and artistic qualities. These schools establish and follow curriculums that are suited to achieving the education objectives guaranteed by the Gifted Education Promotion Act and its Enforcement Decrees. This study compares the curriculums and curriculum tables of the science schools for the gifted to those of the science and art schools for the gifted to evaluate their methods of operation and performance. Additionally, it determines which curriculums provide an opportunity for students to nurture convergent thinking, and discusses how suitable curriculums could be implemented to develop convergent thinking.
Keywords: Curriculum evaluation; Gifted school; Math-Oriented Convergent education